THE ROLE OF EPITHELIAL-TO-MESENCHYMAL TRANSITION AND AUTOPHAGY IN ANTITUMORAL RESPONSE OF MELANOMA CELL LINES TO TARGET INHIBITION OF MEK AND mTOR KINASES - A. S. Lozhkomoev; O. V. Bakina; A. N. Fomenko; A. V. Avgustinovich; S. G. Afanasyev; A. Yu. Dobrodeev; L. V. Spirina; A. S. Tarasova; U. B. Urmonov (Сибирский онкологический журнал)
Introduction. Cutaneous melanoma is a challenge to treat due to rapid progression of disease and acquired resistance to therapy. Autophagy and the epithelial-to-mesenchymal transition (EMT) are closely interrelated and play a key role in tumor progression. Targeted co-inhibition of MEK and mTOR kinases is a potential target for melanoma therapy by downregulatoin of the EMT.Objective: to study the effect of MEK and mTOR co-inhibition on cell viability, ability to form 3D-spheroids and migratory capacity of melanoma cell lines, and correlation of these changes with EMTand autophagy-related markers.Material and Methods. Melanoma cell lines Mel Z and Mel MTP were derived from patients, who were treated at the N.N. Blokhin National Medical Research Center of Oncology. The antiproliferative effect of binimetinib and/or rapamycin was studied by the MTT -test. 3D spheroids were formed using RGD peptides. Cell migration and invasion were assessed by a Boyden chamber migration assay. The expression levels of autophagy and EMT markers were investigated by immunocytochemistry or immunoblotting.Results. Rapamycin increased cytotoxicity of binimetinib in both 2D and 3D melanoma cell line cultures. At the same time, binimetinib and rapamycin reduced invasion, but not migration capacity of melanoma cells in vitro. The effectiveness of the combination was associated with a decrease in the EMT markers (N-cadherin and β-catenin) and autophagy markers (Beclin 1, p62/SQST M1 and LC3BII ) in melanoma cells.Conclusion. Inactivation of autophagy and EMT leads to overcoming the resistance to current anti-melanoma therapy and can be considered as a promising target for the treatment of melanoma.